2012
DOI: 10.1681/asn.2011030273
|View full text |Cite
|
Sign up to set email alerts
|

Anti–LAMP-2 Antibodies Are Not Prevalent in Patients With Antineutrophil Cytoplasmic Autoantibody Glomerulonephritis

Abstract: Lysosomal membrane protein 2 (LAMP-2) is a target of antineutrophil cytoplasmic autoantibodies (ANCA) in addition to the more commonly known targets proteinase 3 and myeloperoxidase. The prevalence of anti-LAMP-2 antibodies and their relationship to disease in ANCA glomerulonephritis are not well described. We measured anti-LAMP-2 reactivity in 680 sera samples (two academic centers) from patients with ANCA glomerulonephritis (n=329); those with ANCA-negative glomerulonephritis (n=104); those with fimbriated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 13 publications
3
77
2
4
Order By: Relevance
“…In applying them to new European cohorts from three different centers, we confirm that antibodies to hLAMP-2 are highly prevalent in patients with piFNGN both at presentation and during clinical relapse. Results of sequential measurements after the start of treatment provide a possible explanation for the disparity between our findings and those of Roth et al 18 Figure 1. cDNA constructs, generation, and quality control of recombinant hLAMP-2. (A) Representation of cDNA encoding hLAMP-2A with the 28 amino acid leader peptide (LP), 347 amino acid extracellular domain, 24 amino acid transmembrane domain (TM), and 11 amino acid cytoplasmic domain (Cytopl).…”
contrasting
confidence: 86%
“…In applying them to new European cohorts from three different centers, we confirm that antibodies to hLAMP-2 are highly prevalent in patients with piFNGN both at presentation and during clinical relapse. Results of sequential measurements after the start of treatment provide a possible explanation for the disparity between our findings and those of Roth et al 18 Figure 1. cDNA constructs, generation, and quality control of recombinant hLAMP-2. (A) Representation of cDNA encoding hLAMP-2A with the 28 amino acid leader peptide (LP), 347 amino acid extracellular domain, 24 amino acid transmembrane domain (TM), and 11 amino acid cytoplasmic domain (Cytopl).…”
contrasting
confidence: 86%
“…There are currently no clinical-grade assays for measuring hLAMP-2, necessitating our use of three independent assays. We and others are working intensively to develop assays suitable for general use; however, the results reported here caution against the use of heavily glycosylated hLAMP-2 preparations as assay substrates, 22 such as those expressed in human embryonic kidney 293 cells, because of the risk that pathogenetically relevant epitopes will be occluded and that autoantibodies to them will go undetected.…”
Section: Discussionmentioning
confidence: 92%
“…18,19,21 Although another group reported a lower overall incidence, the frequency of anti-hLAMP-2 antibodies at presentation in their cohort was still highly significantly increased, with a frequency 10-fold higher than healthy controls. 22 …”
mentioning
confidence: 99%
“…Roth et al [137] however found no correlation between LAMP2 titres and disease activity. Their data do not support a mechanistic relationship between anti-LAMP-2 antibodies and ANCA glomerulonephritis.…”
Section: Nephrology 2011 Updatementioning
confidence: 92%
“…monoclonal gammopathy. The most common complement related disease with MPGN is atypical haemolytic uraemic syndrome (HUS), which may be caused by inherited (often familial) polymorphism of factor H -a downregulating component of the complement system -or acquired antibodies against factor H. Finding a primary cause of MPGN may have a paramount effect on its proper therapy [137,138].…”
Section: Nephrology 2011 Updatementioning
confidence: 99%